Five years of monitoring for the emergence of oseltamivir resistance in patients with influenza A infections in the Influenza Resistance Information Study (IRIS) - Lina, Bruno; Boucher, Charles; Osterhaus, Albert; Monto, Arnold S.; Schutten, Martin; Whitley, Richard J.; Nguyen-Van-Tam, Jonathan S. (Wiley Open Access, 2018)
Background and Objectives: The Influenza Resistance Information Study (IRIS) was initiated in 2008 to study the emergence of neuraminidase inhibitor (NAI) resistance and the clinical course of influenza in immunocompetent treated and untreated patients.